Salvianolic Acid B and Ginsenoside Re Synergistically Protect Against Ox-LDL-Induced Endothelial Apoptosis Through the Antioxidative and Antiinflammatory Mechanisms - Ke Yang; Ke Yang; Ke Yang; Ke Yang; Yun Luo; Yun Luo; Yun Luo; Yun Luo; Shan Lu; Shan Lu; Shan Lu; Shan Lu; et al. (Frontiers Media S.A., 2018)
Salvianolic acid B (SalB) and ginsenoside Re (Re) protect endotheliocytes against apoptosis through different mechanisms. However, whether both compounds could synergistically protect endothelial cells against oxidized low-density lipoprotein (Ox-LDL)-induced apoptosis is unclear. This study aimed to assess the protective effect of combined SalB and Re (SR) treatment on Ox-LDL-induced endothelial apoptosis and to explore the mechanism underlying this effect. Results showed that SalB, Re, or SR could protect against Ox-LDL-induced endothelial apoptosis. Furthermore, the composition of SR was optimized through central composite design with response surface methodology. SR with a composition of 60 μg/mL of SalB and 120 μg/mL of Re exerted the optimal protective effect. Network pharmacology research revealed that SalB and Re in SR synergistically protect against Ox-LDL-induced endothelial apoptosis by regulating oxidative stress and phlogistic pathways. In vitro experiments confirmed these results. Compared with the same dose of SalB or Re alone, SR significantly decreased the contents of inflammatory mediators and increased the activities of antioxidant enzymes. SR could synergistically restore the balanced redox state of the cells and inhibit the activation of nuclear transcription factor kappa B and the caspase cascade by activating the phosphatidylinositol 3 kinase/protein kinase B pathway and inhibiting the phosphorylation of p38 mitogen-activated protein kinase. These pathways are regulated by down-regulating the expression of lectin-like Ox-LDL receptor-1 and NADPH oxidase and up-regulating the expression of estrogen receptor alpha. Therefore, SR effectively prevents Ox-LDL-induced endothelial apoptosis through antioxidative and antiinflammatory mechanisms.